Persistence of wetlands on North Stradbroke Island (south‐east Queensland, Australia) during the last glacial cycle: implications for Quaternary science and biogeography. (August 2017) - Tibby, J.; Barr, C.; Marshall, J. C.; McGregor, G. B.; Moss, P. T.; Arnold, L. J.; Page, T. J.; Questiaux, D.; Olley, J.; Kemp, J.; Spooner, N.; Petherick, L.; et al.
ABSTRACT: Few Australian wetlands have persisted since the Last Glacial Maximum, with fewer still in existence through the entire last glacial cycle. The absence of wetlands, which itself indicates periods of moisture deficit, means there are few continuous climate and environmental change records covering this critical period. The lack of wetland persistence also raises the question of how plant and animal species that require permanent wetlands survived the last glacial cycle. Sixteen wetlands have been cored and dated on North Stradbroke Island (Minjerribah) – a large east Australian sand island – with basal dates reported from 10 sites for the first time. These wetlands range in age to over 200 000 years old, with six dating to the Last Glacial Maximum or earlier. There is no evidence of a stratigraphic discontinuity in the radiocarbon‐based age–depth profiles, suggesting continuous deposition of highly organic sediment through the period covered by these ages ( c . 40 ka). The persistence of these wetlands suggests that for much of the last 40 000 years, and for perhaps much longer, the regional moisture balance has been positive. Over the last glacial cycle, persistently wet conditions may have provided a refuge from regional drying, and thus contributed to the high genetic diversity of rainforest plants in the region. Vegetation and climate records from these sites will allow hypothesis testing about the drivers of both local and regional climate variability. Copyright © 2017 John Wiley & Sons, Ltd.